Comparative effects of MKARE® eggshell membrane and hydrolyzed collagen as nutricosmetics on skin biophysical properties: a randomized clinical trial - González-Rodríguez, Yaiza; La Nuez-García, Manuel A.; Jiménez, Marina; Villar-Suárez, Vega; Casado-Santos, Alejandro (Frontiers in Nutrition, 2026)
IntroductionThis study aimed to investigate the impact of fresh eggshell membrane (MKARE®) as a nutricosmetic ingredient, with a focus on its influence on skin properties. Biomechanical measurement devices were used to assess the effects on skin condition, and the results were compared with hydrolyzed collagen and a placebo.MethodsBiophysical parameters were analyzed (using Cutometer®, Tewameter®, Corneometer®, and VISIA®) among participants showing signs of aging. These individuals consumed either 300 mg of fresh eggshell membrane (MKARE®) or 8,000 mg of hydrolyzed collagen, and the results were compared to a placebo group after 28 and 57 days.ResultsThe results showed significant improvements in skin firmness/flexibility and elasticity after 57 days of MKARE® intake, compared to both the hydrolyzed collagen and placebo groups.ConclusionThis study demonstrates that a 300 mg intake of fresh membrane MKARE® positively affects mechanical skin parameters compared to the group that consumed 8,000 mg of hydrolyzed collagen or the placebo group. These improvements suggest that MKARE® consumption regenerates the skin structure, primarily due to positive changes in collagen and elastin formation, which are key contributors to the improvement of skin firmness, elasticity, and barrier protection.